Eleni-Anna Chlepa, Byzantine Monuments in Modern Greece. Ideology and Practice of Restorations 1833-1939. - Cormack , Robin (Journal of Greek Archaeology, 2024)
This important book was first published in Greek in 2011, and it was immediately obvious that the author had systematically worked through archives and other sources to produce the most detailed account of restorations made in Byzantine monuments since 1833. I should say that the 2011 publication helped significantly to improve articles I myself wrote in 2013 about the mosaics of the monastery at Daphni. With welcome support from the A.G. Leventis Foundation, the Greek publisher Kapon has now brought out this English translation. The text is unchanged and there is a list of some related publications which have appeared since 2011. Without doubt it can be said that any work on Byzantine monuments in Greece must check any material evidence recorded in this systematic and detailed survey.